PENGARUH RANGGAS PAKSA DAN SUPLEMENTASI TEPUNG BEKICOT TERHADAP PERTUMBUHAN FOLIKEL YOLK AYAM (Gallus turcicus) - Kiptiyah, Hartanto, Lisin (Lembaga Penelitian dan Pengembangan Universitas Islam Negeri Maulana Malik Ibrahim Malang., 2011)
Research is conducted to examine the effect of fast method’s forced molting and snail flour supplementation on yolk follicle growth of chicken (Gallus turcicus). In this research, female chicken is used with 1.5 years of age and 1.2 ± 2 kg body weight. The treatments include the fast method’s forced f molting (without food for 0 hour, 72 hours, and 168 hours, but with drink ad libitum) and snail flour supplements of 6 %, 12 %, and 18 %. The observation is concerned with yolk follicle growth attributes such as ovary weight and yolk follicle sizes, such as large, medium and small. The data obtained is analyzed by ANOVA. Result indicates that the treatment of fast method’s forced molting and snail flour supplementation does not have effect on yolk follicle growth of chicken (Gallus turcicus). It is evident as reviewed from the ovary weight and from yolk follicle sizes of large, medium and small. Such phenomena is revealed through data related to fast method’s forced molting and snail flour supplementation, in which both are without effect on ovary weight and large follicle size, but with effect on medium and small yolk follicle sizes.Keywords: Chicken, forced molting, snail flour, yolk follicle